PENGARUH STRES KERJA, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASIONAL PERAWAT DI RUMAH SAKIT JIWA MUTIARA SUKMA MATARAM PROVINSI NTB - Pitri, Nurhidayatul (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This study aims to analyze the significance of the influence (1) job stress on organizational commitment, (2) compensation for organizational commitment, (3) career development towards organizational commitment of nurses at Mutiara Sukma Mental Hospital. This type of research is causality research using questionnaire techniqueas the main technique of data collection. The population and respondent this study is all the nurses at Mutiara Sukma Mental Hospital Mataram which amounted to 71 people. The results of the study showed that: (1) Work stres had negative and insignificant effect on organizational commitment, (2) Compensation had positive and significant effect on organizational commitment, (3) Career development had significant positive effect on organizational commitment, and (4) Compensation is the most dominantinfluence on organizational commitment. Keywords: Job Stress, Compensation, Career Development, and Organizational Commitment.